PEMBUATAN BACK-END WEBSITE ORGANISASI PD IGRA KOTA BOGOR - Marsudi, Ilham; Kusumah, Fitrah Satrya Fajar (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
Organizational web is one of its types, with organizational web it is something that is very beneficial for certain organizations. In Indonesia, the organization's web has been widely used because it makes it easier to find information about the organization. When the current pandemic situation makes it impossible to meet face-to-face to find information, the organization's web is in great demand by many people because in addition to making it easy, it can also reduce the cost of spending, which used to print brochures every time you want to provide certain information, now you just need to enter it into the web. the. The purpose of this research is to create a back-end website, to manage data bulletins/news, announcements, agendas, galleries, and teachers on the IGRA website. The research method used is the waterfall. Making the back-end website of the Bogor City PD IGRA Organization, namely, making it easier to provide information such as news, agendas, or announcements via online, and can be accessed easily without having to write letters. On the Back-end Website, PD IGRA can add, modify, and delete data. Accessible via administrator login with available account.